ANALISIS KEMAMPUAN BERPIKIR KREATIF SISWA SMP DALAM MEMAHAMI KONSEP SIMETRI DAN TRANSFORMASI MELALUI EKSPLORASI MOTIF BATIK GEDOG TUBAN - Amelia Nur Fajrin; Faridah, Luluk; Khafidhoh Nurul Aini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze junior high school students' creative thinking skills and conceptual understanding of symmetry and geometric transformation through the exploration of Tuban Gedog Batik motifs. Creative thinking is analyzed using four indicators (fluency, flexibility, originality, and elaboration), while conceptual understanding is analyzed using four indicators (restating a concept, classifying objects with examples and non-examples, presenting a concept in various forms of representation, and using or applying a concept). The background of this research is the low level of students' creative thinking skills and conceptual understanding in mathematics learning, especially in geometry. The study employs a qualitative descriptive approach. Research subjects consist of students representing high, medium, and low mathematical ability. Data are collected through tests, interviews, observations, and documentation and analyzed using the Miles and Huberman model.